Comparative Voyage-Based Evaluation of Yacht Transfer by Self-Sailing and Cargo Vessel Shipment – A Pilot Study - Ülker, Duygu; Koldemir, Birsen (Promet - Traffic&Transportation, 2021)
The seasonal domestic yacht traffic direction in Turkey from the Marmara Sea and South coasts of Turkey at the beginning of the Summer and opposite direction at the end of the Summer or beginning of the Autumn. Considering the long-distance and long sailing time between the routes of seasonal yacht moving, this study revealed whether the yacht carrying in domestic shipping can be feasible for yacht owners and ship owners. The technical and managing perspective of port and ship selection criteria are indicated for yacht carrying. Estimations are done for the selected sample ship and yacht model and selected loading/discharging ports. All of the voyage expenses are formulated and written in MatLab. The voyage costs of the sample ship and yacht model are estimated to evaluate the feasibility of yacht carrying between the Bodrum and Haydarpaşa Port. The cost of a yacht carrying between the ports is acceptable depends on the number of yachts, speed of yacht and yacht type carried. The long coastline and yacht traffic potential of Turkey give the opportunity of effectiveness for shipping of yachts in the domestic line.